2016
DOI: 10.1177/0095798415604796
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Identity Invalidation for Black Multiracial People

Abstract: Multiracial people report repeated experiences of racial identity invalidation, in which their racial identity is rejected by others. The current study examined whether the race of the perpetrator of these invalidating experiences matters in determining the impact of invalidation. A sample of 221 Black multiracial people was recruited to take an online survey investigating their experiences of identity invalidation, levels of cultural homelessness, and challenges with racial identity. Participants reported tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 46 publications
0
48
0
Order By: Relevance
“…This question is important to address in order to understand the size, scope, and heterogeneity within current definitions of Blackness, which has implications for the community's resource allocation and political power (Rockquemore & Laszloffy, 2003). Furthermore, addressing whether Biracial people are accepted within Black spaces has implications for the racial identity development, belonging, social support, and discriminatory coping, and subsequently, the mental health, of Biracial individuals (Franco & Franco, 2015;Shih & Sanchez, 2005;Sanchez, 2010). The present study is thought to create a foundation for addressing this question, through the development of the BGMS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This question is important to address in order to understand the size, scope, and heterogeneity within current definitions of Blackness, which has implications for the community's resource allocation and political power (Rockquemore & Laszloffy, 2003). Furthermore, addressing whether Biracial people are accepted within Black spaces has implications for the racial identity development, belonging, social support, and discriminatory coping, and subsequently, the mental health, of Biracial individuals (Franco & Franco, 2015;Shih & Sanchez, 2005;Sanchez, 2010). The present study is thought to create a foundation for addressing this question, through the development of the BGMS.…”
Section: Discussionmentioning
confidence: 99%
“…Also, further replications of the scale with diverse samples should also include additional measures of reliability, such as test-retest reliability, and discriminant validity. Future research might determine predictors of perceptions of Biracial group membership so that Biracial people might be able to seek out specific affirming spaces within the Black community, as Biracial people often experience racial isolation and affirming relationships have been found to prevent against discriminatory experiences (Franco et al, 2016), and affirmation by Black people has been shown to be particularly important to Biracial people's racial identity (Franco & Franco, 2015). In a qualitative study conducted by Franco et al (2016), some factors found to contribute to Black/White Biracial people's rejection included their White heritage, and their non-racially prototypical phenotype and failure to perform racially stereotypical behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These include, among other things: what the person looks like (Doyle and Kao 2007; Herman 2004; Khanna 2004), what they’ve been told and by whom (Brunsma 2005; Childs 2006; Franco and Franco 2015; Roth 2005), their social connections and cultural exposure (Khanna 2004; Liebler 2001, 2004; Miville et al 2005), what other people assume about them (Campbell and Troyer 2007; Rockquemore and Brunsma 2002; Penner and Saperstein 2008), and their experiences with discrimination (Miville et al 2005; Waters 1999). Each of these factors is moderated by other characteristics such as age, sex, socioeconomic status, nativity, and characteristics of others nearby (Alcoff 2006; Penner and Saperstein 2013; Porter et al 2015; Root 1990, 1996).…”
Section: Conceptual Model and Prior Researchmentioning
confidence: 99%